Changes in self-reported alcohol consumption at high and low consumption in the wake of the COVID-19 pandemic: a test of the polarization hypothesis - Tran, Alexander; Jiang, Huan; Lange, Shannon; Štelemėkas, Mindaugas; Stumbrys, Daumantas; Tamutienė, Ilona; Rehm, Jürgen (Frontiers in Psychiatry, 2025)
BackgroundThe Coronavirus Disease 2019 (COVID-19) pandemic and associated public health measures impacted alcohol use. It was hypothesized that the COVID-19 pandemic led to a polarization of drinking–that is, heavy drinkers increased their drinking, while light to moderate drinkers decreased their drinking. The aim of the current study was to probe deeper into this hypothesis to determine precisely which segment of heavy drinkers increased their consumption.MethodsWe obtained data from the Reducing Alcohol Related Harm Standard European Alcohol Survey for Lithuania, for two separate years; 2015 (n = 1354, mean age = 41.04 ± 13.04, females = 680, 50.2%) and 2020 (n = 1015, mean age = 42.27 ± 13.44, females = 513, 50.5%). Average daily consumption (in grams per day) was decomposed into deciles and compared pre-COVID-19 to onset of the COVID-19 pandemic across the 10th, 9th, and 1st deciles. To test our hypothesis we conducted a non-parametric pairwise comparison (Mann-Whitney U test) of alcohol consumption at the upper deciles. We also conducted a multivariate linear regression using mental well-being and sociodemographic variables as predictors of consumption.ResultsAlcohol consumption decreased from 2015 to 2020, mean = 11.49 cl of pure alcohol (SD = 8.23) vs. mean = 10.71 cl of pure alcohol (SD = 12.12), p <.00001, respectively. However, in the highest decile there was an increase from 2015 to 2020 mean = 29.26 cl of pure alcohol (SD = 5.44) vs. mean = 39.23 cl of pure alcohol (SD = 20.58), p = .0003, respectively. This reversal pattern was not observed in the second highest nor the lowest decile. The multivariate model was significant (F(11,1881) = 20.85, p <.00001, adjusted R2 = 0.10) and showed significant year by sex interaction (p = .021) and year by occupation interaction (p = .023) on alcohol consumption.ConclusionAlthough COVID-19 was associated with declines in alcohol consumption, in Lithuania it appears that there was an increase in consumption among the heaviest drinkers, driven partially by a smaller difference in consumption between males and females.